OPTIMASI LETAK SHEAR WALL PADA STRUKTUR GEDUNG - Samsul A Rahman Sidik Hasibuan; Faqih Ma’arif (JMTS: Jurnal Mitra Teknik Sipil, 2022)
Shear walls are structural walls designated as part of an earthquake force-resisting system, which also serves to increase the stiffness of the structure and absorb large shear forces as the height of the structure increases. When shear walls are placed in the right and strategic position, shear walls can be used economically to provide horizontal load resistance. In this paper, the 7-storey symmetrical building structure is modelled and analyzed using ETABS v.9.7.4 software. Analysis was carried out on four structural models with variations in the proposed shear wall locations. The model without shear walls was used as a controller for the normal model. This paper aims to optimize the location of the shear wall in a 7-storey symmetrical building structure. Furthermore, the results of the analysis of the structure of the building without shear walls and variations in the location of the shear walls were obtained using the ETABS v.9.7.4 software. The analysis results show that model 3 is a better location for shear walls to be applied to the review structure.   Abstrak Shear wall merupakan dinding struktur yang ditetapkan sebagai bagian dari sistem penahan gaya gempa, juga berfungsi menambah kekakuan struktur dan menyerap gaya geser yang besar seiring dengan semakin tingginya struktur. Ketika shear wall diletakan pada posisi yang cocok dan strategis, shear wall dapat digunakan secara ekonomis untuk menyediakan tahanan beban horisontal yang diperlukan. Dalam tulisan ini struktur gedung simetris 7 tingkat dimodelkan dan dianalisis menggunakan software ETABS v.9.7.4. Analisis dilakukan pada 4 model struktur dengan variasi letak shear wall yang diusulkan. Untuk model normal yaitu model tanpa shear wall digunakan sebagai pengontrol. Tulisan ini bertujuan untuk mengoptimalkan letak shear wall pada struktur gedung simetris 7 tingkat. Selanjutnya, hasil analisis struktur gedung tanpa shear wall dan dengan variasi letak shear wall menggunakan software ETABS v.9.7.4 telah diperoleh. Hasil analisis menunjukan bahwa model 3 merupakan letak shear wall yang lebih baik untuk diterapkan pada struktur tinjauan.